Ateísmo y espiritualidad - Estrada, SJ, Juan Antonio (Razón y fe, 2019)
In the last century, the secularization of society, the secularization of the State and the scientific-technical revolution were linked to the progressive disappearance of religion in the public sphere, the loss of influence of churches and the privatization of faith. Fifty years later, religion is still present in society, despite the religious crisis. Not only has society changed, but also religion, faced with new challenges and possibilities. Although there has been a decline in religious influence on culture, religion is far from disappearing. On the contrary, currents and movements are emerging that denote interest in it, even if they admit the truth of secularization and laïcité. Two new approaches opened up unforeseen possibilities fifty years ago: philosophical movements propelling a religion without God and a secular spirituality; and worldviews offering a religious but not a Christian spirituality, rejecting the personal God of biblical monotheisms, Judaism, Christianity and Islam. We will briefly indicate some features of these approaches and the possibilities they open to Christianity